(untitled) (Medical Forum Monthly, 2024)
Objective: The present study determined the predictive significance of mean platelet volume (MPV) and low platelet count (thrombocytopenia) as hematological indicator of patient outcome in medical intensive care units (ICU). Study Design: Observational study. Place and Duration of Study: This study was conducted at the Department of Pathology and Medical ICU, Indus Medical College Hospital, Tando Muhammad Khan, Sindh from April 2017 to March 2019. Materials and Methods: Critical subjects admitted to medical intensive care units of the hospital were selected according to inclusion and exclusion criteria. A sample of 300 (n=300) patients was selected and analyzed to meet criteria of study. 5-10 ml of venous blood sample was collected for study parameters. Data was analyzed on SPSS 21.0 IBM, Incorporation USA at 95% confidence interval. Results: Thrombocytopenia was noted in 70 (23%) and severe thrombocytopenia in 19 (6.3%) patients (P=0.0001). Thrombocytopenia and severe thrombocytopenia were noted in 14 (4.6%) of non- survivors vs. (1.6%) in survivors (P=0.0001). Normal and elevated MPV in survivors and non- survivors were noted in 195 (65%) vs. 40 (13.3%) and 14 (4.6%) vs. 51 (17%) respectively (P-0.0001). Platelet counts and MPV in survivors and non- survivors were noted as 378457±459 vs. 123153±366 (x109/L) (P=0.0001) and 9.83±1.23 vs. 14.73±3.53 fl respectively (P=0.0001). ROC curve shows area under curve (AUC) of 0.913 (91.3%) (P=0.0001). Conclusion: Thrombocytopenia and elevated MPV are useful hematological indicators to predict the poor patient outcome and mortality.